Al-Madhāhib al-Ṣūfīyah fī Falimbānj fī al-Qarnayn al-Thāmin ‘Ashr wa al-Tāsi’ ‘Ashr - Syahid, Ahmad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2001)
This article attempts to trace the Islamic intellectual tradition of Palembang praying particular attention to the scholarly form that was shaped and molded by the Ulama. In addition, this article attempts to identify the characteristics of the Palembang Ulama, and draw comparisons between this group and the Ulama of the earlier Sufi period in Aceh. Of the several Ulama of Palembang who are the focus of this article, the most important are Shihab al-Din bin 'Abd Allah Muammad, Kemas Fakbr al-Din, Muhammad Muhyi al-Din, and of course, the most prominent, 'Abd al-Samad al-Falimbaani.DOI: 10.15408/sdi.v8i2.690